Decision support and forecasting system - Nyakudya, Nigel (Midlands State University, 2019)
To begin with DSW didn’t have a proper software to capture and report its daily activities expediently, the espousal of the M&E department in the organisation reviewed a high frequency of data discrepancies and anomalies in the company records, which then triggered the company to have an interest on investing in a more current, secure, fluid and comprehensible system that is partially intelligent to gear up the decision making process while being able to be associated with any of the existing business activities from selling, budgeting, human resource management and more which integrates every facet of the business into one capable environment. Data mining being a modern concept that seems to be helping many organisations in doing business, DSW will be using the data captured to influence decision making processes and any support that the business really needs. With the help of Java programming language and JavaFX framework the developer found it easy to integrate some of the user requirements into a single system that can forecast the product performance, do product time series analysis whilst monitoring the customer buying patterns and hopping to add some of or all the future user novel requirements to the system if possible. Interviews, observations and questionnaires gathered some of the key data needed to develop the system with the intention to understand how the business tackles their activities in terms of data capturing, reporting and other procedures. With the help of the feasibility analysis it was possible to determine the Storekeeper-DSS achievability. Alternatives were assessed and the development was to be done inhouse using organisational resources and the best changeover strategy was for the system to run alongside the existing system serving the same purpose in smaller groups to avoid losses in the event of a system failure. The proactive and reactive maintenance approaches were put in place to make sure that the system continue to run as required and to make sure that the additional requirements will be added to the new system.